ANALISIS PENGARUH EXPERIENTIAL MARKETING TERHADAP KEPUASAN KONSUMEN (Studi Kasus pada Sop Buah â€œXâ€ kota Semarang) - Lullulangi, Irene Rosa; Sutopo, Sutopo (Faculty of Economics and Business Diponegoro University, 2014)
This research aims to analyze the influence of experiential marketing to customers satisfaction of Â Sop Buah â€œXâ€ in Semarang on Tembalang nearby Universitas Diponegoro. This research consists of dependent variable which is customer satisfaction (Y) and five independent variables which are experiential marketing consists of sense (X1), feel (X2), think (X3 ) , act (X4) and relate (X5). The population of the research is the customer of Sop Buah â€œXâ€ who have purchased more than two times with a sample of 100 respondents. The sampling technique that is used in this research is purposive sampling (judgement sampling), then the data was processed by multiple regression analysisThere were five hypotheses being tested in this study, all of them are acceptable. This condition Â indicates Â that Â all Â of Â five Â variables Â have Â positive Â influence Â on Â the Â application Â ofexperiential marketing on customers satisfaction of Sop Buah â€œXâ€ in Semarang, namely: sense, feel, think, act and relate. The result shows that the research model can be accepted. Adjusted R square showed at moderate level 52,4 %. It mean 47,6 % was explained by other factor which were not examined in this search.